Treatment Guidelines for Atopic Dermatitis Since the Approval of Dupilumab: A Systematic Review and Quality Appraisal Using AGREE-II - Ghazal, Stephanie; Ridha, Zainab; D'Aguanno, Kathleen; Nassim, David; Quaiattini, Andrea; Netchiporouk, Elena; Poulin, Yves; Kalia, Sunil; Marcoux, Danielle; Piguet, Vincent; Jack, Carolyn (Frontiers in Medicine, 2022)
Introduction Since its approval for adults with moderate-to-severe atopic dermatitis (AD) in 2017, dupilumab has been incorporated into clinical practice guidelines (CPGs). However, recommendations differ internationally, and quality assessment of their development is unclear. Objective We aimed to systematically review and appraise the quality of CPGs for adult AD reported since 2017 and map the recommendations for dupilumab initiation relative to conventional systemic therapy (CST). Materials and Methods A literature search was conducted in June 2020 in MEDLINE, EMBASE, SCOPUS and CINAHL. Twelve CPGs were retrieved. Methodological quality was assessed using the validated Appraisal of Guidelines for Research & Evaluation II tool (AGREE-II). Recommendations were extracted and compared. Results CPGs’ AGREE-II median scores per domain were (%, r=range): scope/purpose, 78% [50-96]; stakeholder involvement, 54% [28-85]; rigor of development, 39% [21-63]; clarity of presentation, 85% [69-100]; applicability, 27% [6-51]; and editorial independence, 76% [42-100]. None met threshold of 70% quality criteria for rigor of development nor the applicability domains. Three CPGs met criteria for recommendation without modification. CPGs’ approach to dupilumab initiation was as follows: second line, preferred over CST and nbUVB (n=1/12 CPG); second line, equivalent to CST or nbUVB (n=3/12 CPGs); third line, after nbUVB or CST (n=5/12 CPGs); fourth line after nbUVB and CST (n=2/12). No consensus was reached for n=1/12 CPG. Conclusion and Relevance Dupilumab is now incorporated into CPGs for adult AD. These CPGs exhibited good quality in scope/purpose, clarity and editorial independence domains. However, none met AGREE-II criteria for methodological rigour/applicability. Gaps were found in: mechanisms for updates, facilitators/barriers, resource implications, and stakeholder involvement. Only n=3/12 CPGs met quality criteria for recommendation without modifications. Of these, two favoured a conservative sequential approach to initiation of dupilumab relative to CST, while one did not reach consensus. Our findings highlight divergent recommendations AD treatment, underlining a need to incorporate quality criteria into future guideline development.